2012
DOI: 10.1111/j.1742-481x.2012.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Suction assisted pulse lavage: randomised controlled studies comparing its efficacy with conventional dressings in healing of chronic wounds

Abstract: Chronic, open, non-healing wounds pose a continual challenge in medicine as the treatment is variable and there are no documented consistent responses. Although wound aetiologies vary and there are a number of factors that affect chronic wound pathogenesis, wound ischaemia and bacterial colonisation of wounds are the chief concerns among them. Conventionally, pulse lavage has been used primarily as a wound debriding device. To address both the critical factors of wound ischaemia and bacterial burden, a couple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The authors concluded that pulsatile lavage significantly reduced wound size, bacterial load, and time to definitive wound closure ( p < 0.001) compared with gravity flow irrigation. 13…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that pulsatile lavage significantly reduced wound size, bacterial load, and time to definitive wound closure ( p < 0.001) compared with gravity flow irrigation. 13…”
Section: Resultsmentioning
confidence: 99%
“…If the sites of irrigation need to be changed, the position of patients need to be changed repeatedly. This process may aggravate the injury, destroy the biological barrier, and make the patient more susceptible to infection [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 This finding has been substantiated by multiple other studies, showing that pulsed irrigation removes bacteria from contaminated bone and leads to reduced size and faster healing of chronic wounds. 9,23 Since the efficacy of wound irrigation correlates with the irrigant pressure, there are many benefits of using pulsed lavage compared to low-pressure irrigation. Although low-pressure irrigation is efficacious in removing bacteria from wounds and surgical sites, several studies have shown that pulsed irrigation is even more effective in removing bacteria from surgical wounds and orthopedic implants, compared to low-pressure irrigation, even when using less irrigant.…”
Section: Discussionmentioning
confidence: 99%